SMALLHOLDER DAIRYING ZIMBABWE - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
The dairy sector in Zimbabwe consists of two strongly contrasting categories of producers: the large-scale commercial producers with an average milking herd in excess of 100 cows using modern technology to achieve high output per cow; and the...